Umbilical cord mesenchymal stromal cells—from bench to bedside - Chetty, Shashank; Yarani, Reza; Swaminathan, Ganesh; Primavera, Rosita; Regmi, Shobha; Rai, Sravanthi; Zhong, Jim; Ganguly, Abantika; Thakor, Avnesh S (Frontiers in Cell and Developmental Biology, 2022)
In recent years, mesenchymal stromal cells (MSCs) have generated a lot of attention due to their paracrine and immuno-modulatory properties. MSCs derived from the umbilical cord (UC) are becoming increasingly recognized as having increased therapeutic potential when compared to MSCs from other sources. The purpose of this review is to provide an overview of the various compartments of UC tissue from which MSCs can be isolated, the differences and similarities with respect to their regenerative and immuno-modulatory properties, as well as the single cell transcriptomic profiles of in vitro expanded and freshly isolated UC-MSCs. In addition, we discuss the therapeutic potential and biodistribution of UC-MSCs following systemic administration while providing an overview of pre-clinical and clinical trials involving UC-MSCs and their associated secretome and extracellular vesicles (EVs). The clinical applications of UC-MSCs are also discussed, especially in relation to obstacles and potential solutions for their effective translation from bench to bedside.